Evaluación de un protocolo de sincronización de celo para receptoras en vacas criollas adicionando una fuente exógena de GNRH y LH en el momento del celo - González Briceño, Rudbel Leobar (2013)
Were used nine native bovine females in the Southern Region of Ecuador (CSR) divided into three protocols of synchronization of estrus to receptors, the Protocol used was: day zero were applied intravaginal devices (DIB®-Sintex) impregnated with 50 mg of fluorogestone acetate plus 2 mg of estradiol benzoate (BE) and plus 50 mg progesterone (P4), day 7 applied to 400 IU of equine chorionic gonadotropin (eCG), day eight remove the DIB and more 2 ml of Prostaglandin (PGF2α), day nine was applied 1 mg of BE, the only difference was that in the treatment one in the day 10 was applied GNRH, in treatment two LH and treatment three was the control then the day 16 observe the size of the corpus luteum through ultrasound. For each of the variables analyzed was carried out an ADEVA, and when there was statistical difference (P> 0.05) was applied the Duncan test; the variables studied were: size of ovaries at the beginning of treatment where was obtained an average of 22.5 mm in the three treatments, also was measured the time for submission of manifest estrus towards removal DIB where was obtained an average time of 30.1 hs in three treatments; the duration and intensity of the estrus in the three treatments was 21.1 hs and the intensity of 78%, in addition all the UE presented evident estrus with a 91.0% of the presented symptoms; also was determined the size of pre-ovulatory follicle through an ultrasound getting an average size of 12,5 mm in all of these variables there was not statistical difference (P> 0.05); also was assessed the size of the corpus luteum to day seven postestrus where there was obtained statistical difference (P<0.05), presenting in the treatment one and two statistically similar results with a size of corpus luteum of 20 and 20.5 mm respectively and the treatment three 17.1 mm, being all these sizes suitable for the reception of an embryo, responding bovine Creoles favorably to synchronization of estrus treatments investigated, that would help to improve the productive and reproductive parameters in native cattle of CSR.